Unveiling The Impact of Green Accounting and Sustainability Disclosure On The Firm Value - Abdullah Aziz Alaika; Amrie Firmansyah (Journal of Governance Risk Management Compliance and Sustainability, 2024)
This study examined the impact of green accounting and sustainability disclosure on firm value in the Indonesian palm oil industry. The objective was to empirically assess how environmental performance measured by PROPER and sustainability reports affects firm value. Using quantitative research methods, the study analyzed data from 124 palm oil company observations listed on the Indonesia Stock Exchange from 2018 to 2022. The research variables included firm value proxied by Tobin’s Q, green accounting proxied by PROPER scores, and sustainability disclosure indexed from the companies’ sustainability reports. The study also included profitability, firm size, and leverage as control variables. The results indicated that green accounting had a negative impact on firm value, suggesting that environmental compliance imposes short-term financial burdens on companies. However, sustainability disclosure did not significantly influence firm value, indicating that investors in the palm oil industry may prioritize short-term financial performance over long-term sustainability considerations. These findings contribute to the literature on corporate governance and sustainability, particularly in industries with high environmental impact, like palm oil.